Hemodynamic influence of mild stenosis morphology in different coronary arteries: a computational fluid dynamic modelling study - Chen, Xi; Cao, Haoyao; Li, Yiming; Chen, Fei; Peng, Yong; Zheng, Tinghui; Chen, Mao (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction: Mild stenosis [degree of stenosis (DS) < 50%] is commonly labeled as nonobstructive lesion. Some lesions remain stable for several years, while others precipitate acute coronary syndromes (ACS) rapidly. The causes of ACS and the factors leading to diverse clinical outcomes remain unclear. Method: This study aimed to investigate the hemodynamic influence of mild stenosis morphologies in different coronary arteries. The stenoses were modeled with different morphologies based on a healthy individual data. Computational fluid dynamics analysis was used to obtain hemodynamic characteristics, including flow waveforms, fractional flow reserve (FFR), flow streamlines, time-average wall shear stress (TAWSS), and oscillatory shear index (OSI). Results: Numerical simulation indicated significant hemodynamic differences among different DS and locations. In the 20%–30% range, significant large, low-velocity vortexes resulted in low TAWSS (<4 dyne/cm2) around stenoses. In the 30%–50% range, high flow velocity due to lumen area reduction resulted in high TAWSS (>40 dyne/cm2), rapidly expanding the high TAWSS area (averagely increased by 0.46 cm2) in left main artery and left anterior descending artery (LAD), where high OSI areas remained extensive (>0.19 cm2). Discussion: While mild stenosis does not pose any immediate ischemic risk due to a FFR > 0.95, 20%–50% stenosis requires attention and further subdivision based on location is essential. Rapid progression is a danger for lesions with 20%–30% DS near the stenoses and in the proximal LAD, while lesions with 30%–50% DS can cause plaque injury and rupture. These findings support clinical practice in early assessment, monitoring, and preventive treatment.